2012
DOI: 10.3767/003158512x638251
|View full text |Cite
|
Sign up to set email alerts
|

Plectosphaerella species associated with root and collar rots of horticultural crops in southern Italy

Abstract: Plectosphaerella cucumerina, most frequently encountered in its Plectosporium state, is well known as a pathogen of several plant species causing fruit, root and collar rot, and collapse. It is considered to pose a serious threat to melon (Cucumis melo) production in Italy. In the present study, an intensive sampling of diseased cucurbits as well as tomato and bell pepper was done and the fungal pathogens present on them were isolated. Phylogenetic relationships of the isolates were determined through a study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
100
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 41 publications
7
100
0
1
Order By: Relevance
“…The genus Plectosphaerella of the class Sordariomycetes was more abundant on Seodo (2.03%) than on Ulleungdo (0.06%) or Dongdo (0.17%). Members of this genus are known as plant pathogenic fungi (Carlucci et al, 2012). In the class Agaricomycetes of Basidiomycota, the genera Craterellus, Lactarius, Mycena, and Russula were detected only in the Ulleungdo sample, whereas the genus Omphalina was detected only in the Seodo sample.…”
Section: Archaeorhizomycetesmentioning
confidence: 99%
“…The genus Plectosphaerella of the class Sordariomycetes was more abundant on Seodo (2.03%) than on Ulleungdo (0.06%) or Dongdo (0.17%). Members of this genus are known as plant pathogenic fungi (Carlucci et al, 2012). In the class Agaricomycetes of Basidiomycota, the genera Craterellus, Lactarius, Mycena, and Russula were detected only in the Ulleungdo sample, whereas the genus Omphalina was detected only in the Seodo sample.…”
Section: Archaeorhizomycetesmentioning
confidence: 99%
“…According to a report by Carlucci et al (2012), the pathogen resembles P. plurivora and P. pauciseptata. However, little morphological difference is apparent among some species of Plectosphaerella; the species criteria are obscure.…”
mentioning
confidence: 91%
“…According to these characteristics, this fungus appeared to be a Plectosphaerella sp. (Carlucci et al 2012). Perithecia and chlamydospores were absent.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The fungus can cause sudden death and blight disease in a variety of crops (Chen et al, 1999;Harrington et al, 2000). Because P. cucumerina can infect Arabidopsis leaves, the P. cucumerina-Arabidopsis interaction has emerged as a popular model system in which to study plant defense reactions to necrotrophic fungi (BerrocalLobo et al, 2002;Ton and Mauch-Mani, 2004;Carlucci et al, 2012;Ramos et al, 2013). Various studies have shown that Arabidopsis deploys a wide range of inducible defense strategies against P. cucumerina, including JA-, SA-, ABA-, and auxin-dependent defenses, glucosinolates (Tierens et al, 2001;Sánchez-Vallet et al, 2010;Gamir et al, 2014;Pastor et al, 2014), callose deposition (García-Andrade et al, 2011;Gamir et al, 2012Gamir et al, , 2014Sánchez-Vallet et al, 2012), and ROS (Tierens et al, 2002;Sánchez-Vallet et al, 2010;Barna et al, 2012;Gamir et al, 2012Gamir et al, , 2014Pastor et al, 2014).…”
mentioning
confidence: 99%